Wind energy research: State-of-the-art and future research directions. (September 2018) - Willis, D.J.; Niezrecki, C.; Kuchma, D.; Hines, E.; Arwade, S.R.; Barthelmie, R.J.; DiPaola, M.; Drane, P.J.; Hansen, C.J.; Inalpolat, M.; Mack, J.H.; Myers, A.T.; et al.
Abstract: This paper reports the findings from the 2016 Wind Energy Research Workshop held in Lowell, MA. The workshop examined the state-of-the-art in wind energy research within the following three core topic areas: (A) Wind Turbine Design and Manufacturing including: blades, towers/foundations and nacelle, (B) Wind Farm Development including: offshore installations/siting, flow characterization and loads/waves/wind characterization, and (C) Wind Farm Operations including: controls, power production, wind farms, sensing, diagnostics, testing, structural health monitoring, reliability, energy storage, the grid and power transmission. Research challenges and future directions were discussed and are reported for each sub-topic area. Highlights: Wind Turbine Design and Manufacturing, o Wind Turbine Design and Manufacturing (Blades, Towers/Foundations, and Nacelle). Wind Farm Development (Offshore Installations, Flow/Load/Wave Characterization). Wind Farm Operations (Controls, Structural Health Monitoring, Energy Storage/Grid).